A Brief Review on Maximum Flows in Networks with Continuous-Time Settings - Chand, Madan Bahadur; Dhamala, Tanka Nath (Journal of Advanced College of Engineering and Management, 2022)
Discrete and continuous time dynamic flow problems have been studied for decades. The purpose of the network flow problem is to find the maximum flow that can be sent from the source node to the destination node. Our aim is to review the general class of continuous time dynamic flow problems. We discuss about static cut and generalized dynamic cut, the latter one used to prove the maximum flow minimum cut theorem in continuous case.